Male and Female and the Afro-Curaçaoan Household - Marks, A.F (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1976)
The subject of the present study concerns the relationships between men and women and the composition of household groups among the lower Afro-American strata of the society of Curaçao. The material on which it is based was collected in Curaçao in the course of a 15-month period of fieldwork in 1965 and 1966.